A sanctuary of tranquillity in a ruptured world: Evaluating long-term counselling at a women's community health centre. (November 2017) - Ciclitira, Karen; Starr, Fiona; Payne, Nicky; Clarke, Lisa; Marzano, Lisa
The longitudinal study described in this article evaluated long-term counselling provided at a women's health centre in the UK for service users on low incomes. The article focuses on the qualitative aspect of the study in which 59 women were interviewed individually before and/or after their counselling. The interviews explored how women make sense of long-term counselling in the context of their gendered experiences and complex needs. The data were analysed using thematic analysis informed by a feminist orientation and attachment theory. Four main themes emerged: "violence and loss in the context of female oppression", "a sanctuary for women", "non-medicalised long-term counselling in a safe setting", and "benefits of the long view". Participants attributed various benefits to receiving long-term counselling in a women-only environment. These included gaining employment; reduced suicidal ideation, anxiety and depression; improved physical health, improved confidence and being able to make positive changes in their relationships. The women interviewed post-counselling valued long-term counselling in this context, in contrast to short-term therapy in a medicalised environment. Wider implications with regard to clinical practice and research are discussed.